Analisis Performa Jaringan Komputer Menggunakan Teknologi Virtualisasi Untuk Efisiensi Sumber Daya Internet - Rival Ramadhan; Hardiansyah Hardiansyah; Firdiansyah Sundawa (Jurnal Sistem Informasi, Sains Data, dan Informatika, 2026)
The development of information technology presents challenges in managing computer network infrastructure related to resource efficiency and system scalability. This research aims to analyze the performance of computer networks using virtualization technology based on a literature review of previous studies. The research method uses a systematic literature review approach by analyzing 16 scientific publications from international and national journals from the period 2010-2025. The study results show that virtualization has a throughput overhead of 3-7% and latency of 5-10%, but provides resource efficiency of up to 60-80% with an increase in CPU utilization from 15-20% to 70-85%. The trade-off between minimal performance degradation and significant efficiency gains makes virtualization an optimal solution for modern IT infrastructure. This research provides practical recommendations for organizations in adopting virtualization technology